FACTORS AFFECTING THE PERFORMANCE OF FIELD AGRICULTURAL EXTENSIONS IN THE COVID-19 PANDEMIC PERIOD IN PADANG PARIAMAN REGENCY - Faisal Faisal; Martadona Martadona; Dermawan Dermawan (Universitas Perjuangan Tasikmalaya, 2023)
Agricultural instructors must deal with problems in the agricultural sector during the Covid-19 period. The objectives of this study are 1) to analyze the characteristics of agricultural extension workers in the district of Padang Pariaman. 2) Analyzing what factors affect the performance of Field Agricultural Extension Officers during the Covid-19 pandemic. The sampling technique used in this research is census sampling. The data analysis methods used in this research are descriptive qualitative and quantitative analysis using multiple linear regression analysis. The results showed that the characteristics of agricultural extension workers in Padang Pariaman Regency were dominated by female extension workers, with a productive age range of 53-61 years. The most education was Bachelor of Agriculture, with work experience in the range of 12-16 years, with the number of assisted farmer groups 17-61 years. 20, the largest working area with a range of 62-73 km² is two people, while the respondents with the smallest working area in the range of 3.03-14 Km² are 22. Competence is a factor that affects the performance of Field Agricultural Extension Officers (PPL) during the covid-19 period in Padang Pariaman Regency.